Emotional intelligence, job satisfaction and organisational performance in the Malaysian public administration - Supramaniam, Suganthi; Singaravelloo, Kuppusamy (Faculty of Economics and Administration, University of Malaya, 2020)
In the public sector, organisational performance is key to delivering quality services to its stakeholders. Nevertheless, the public service in Malaysia is seen to be less competitive as it only ranks 24th in the World Competitiveness Report in 2017, has worsened from its 12th position in 2014. This study aims to examine the link between emotional intelligence, job satisfaction and organisational performance in the public administration using survey data obtained from 365 administrative and diplomatic officers. The Partial Least Square method is employed to study the link. The findings indicate that emotional intelligence has a positive direct effect on job satisfaction, and similarly, job satisfaction has a positive direct effect on organisational performance. Nevertheless, contrary to the claims of scholars, the study finds no evidence of any significant relationship on the indirect effect of emotional intelligence on organisational performance through the mediating effect of job satisfaction. This further intensifies the need to ensure the job satisfaction of the administrative and diplomatic officers of the public sector is given due attention to move organisational performance forward. © 2020, Faculty of Economics and Administration. All rights reserved.